2008
DOI: 10.5511/plantbiotechnology.25.183
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histochemical characteristics of Japanese birch (Tohoku) plantlets infected with the Inonotus obliquus IO-U1 strain

Abstract: Host-pathogen interactions were investigated on a Japanese birch (Betula platyphylla var. japonica, Tohoku) plantlet after infection with a canker-rot fungus, the Inonotus obliquus IO-U1 strain. For a time-course study, intact, wounded, and infected plantlets were collected from 2 h to 30 days after treatment. Notable changes were observed morphologically in the treated portion of wounded and infected plantlets. Phenolics first deposited at the cut margin and subsequently in vessels after 4 h of infection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In our previous study, host-pathogen interactions were investigated using the Betula platyphylla var. japonica plantlet Tohoku infected with a canker-rot fungus, I. obliquus strain IO-U1 (Rahman et al 2008). We found that phenolic deposition and necrophylactic periderm formation occur as infection-induced responses in B. platyphylla var.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…In our previous study, host-pathogen interactions were investigated using the Betula platyphylla var. japonica plantlet Tohoku infected with a canker-rot fungus, I. obliquus strain IO-U1 (Rahman et al 2008). We found that phenolic deposition and necrophylactic periderm formation occur as infection-induced responses in B. platyphylla var.…”
mentioning
confidence: 79%
“…japonica plantlet Tohoku infected with I. obliquus strain IO-U1. In that study, the fungal hyphae were detected at 10 dpi in cortex, xylem ray, and pith area, although the hyphae did not detected at 2 dpi (Rahman et al 2008 isozymes in the C1, C2, and T plantlets at 2, 10, and 30 d after treatment are shown in Figure 4. Clear isozyme bands were observed in the basic region (pI>8.5), and three POD isozymes (pI 8.5, pI 9.1, and pI 9.3) were induced by wounding and fungal infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We previously investigated the anatomical and histochemical characteristics of living B. platyphylla var. japonica (Tohoku) plantlets infected with the I. obliquus strain IO-U1 for clarifying the host-pathogen interactions (Rahman et al 2008). Our research clarified that phenolics were first deposited at the cut margin tissues and subsequently in the vessels after 4 h of infection; thereafter, their deposition extended to the other xylem elements, cortex, and pith.…”
mentioning
confidence: 76%